1986
DOI: 10.1002/jez.1402400312
|View full text |Cite
|
Sign up to set email alerts
|

Non‐cross‐reactivity of antibodies to murine LDH‐C4 with LDH‐A4 and LDH‐B4

Abstract: The induction of infertility by immunization with the sperm-specific lactate dehydrogenase, LDH-C4, suggests its use in a contraceptive vaccine. Development of an immunological contraceptive for human use, however, requires that there be no cross-reactions with somatic tissues. We have demonstrated, using enzyme-linked immunoabsorbence, solid-phase radioimmunoassay, and competitive inhibition radioimmunoassay, that antisera to LDH-C4 is specific and does not cross-react with the somatic isozymes, LDH-A4 and LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Development of a human contraceptive vaccine relies on the observation that antibodies to LDHC4 do not cross-react with lactate dehydrogenases of somatic tissues (29,33,34). Antibodies to LDHC4, however, do cross-react with the LDHC4 subunits of different species and these reagents have been useful in mapping antigenic determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Development of a human contraceptive vaccine relies on the observation that antibodies to LDHC4 do not cross-react with lactate dehydrogenases of somatic tissues (29,33,34). Antibodies to LDHC4, however, do cross-react with the LDHC4 subunits of different species and these reagents have been useful in mapping antigenic determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the LDH-C4 is intracellular, a small proportion of LDH-C4 is located on the surface of sperm (Wheat & Goldberg 1977). It is also reported that antibodies to LDH-C4 do not cross-react with its somatic isozymes (Liang et al 1986). With these traits, LDH-C4 is an excellent target for the development of a new kind of immunocontraceptive vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have provided impetus for development of an immunologic contraceptive of highly purified sperm-specific antigen such as lactate dehydrogenase-C 4 (LDH-C 4 ). 1,2 Antisera against LDH-C 4 are immunospecific and do not react with somatic LDH-A 4 and LDH-B 4 , 3,4 although this was contradicted in another report. 5 Immunization with heterologous LDH-C 4 by passive or active route reduced fertility in rabbits, mice, and baboons, 1,6 although impairment of fertility by allogenic LDH-C 4 is yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 89%
“…Virgin Balb/c female mice in three different groups were immunized with native LDH-C 4 , Glu-LDH-C 4 , and Gossy-LDH-C 4 . Antigens were emulsified in Al(OH) 3 and 50 mg of each Ag were used for primary immunization through i.r. route.…”
Section: Immunization Protocol and Preparation Of Antiseramentioning
confidence: 99%